THE ALKALI RESERVE OF INTERSTITIAL WATER AT THE SITES OF METHANE EMISSION IN THE SEA OF OKHOTSK - Tishchenko P.Ya.; Pavlova G.Yu.; Nedashkovskii A.P.; Suess E.; Domeier B.; Greinert I. (My University, 2001)
The chemical composition (alkalinity, pH, NH4+, PO43-, Si, H2S, Cl-, Ca2+, and SO42-) of interstitial water was studied in the sediments of the Sea of Okhotsk at sites of methane emission. Variations in alkalinity were observed in the sediments from a typical seawater value (2.3 mM/kg) to 63 mM/kg. It is demonstrated that they are caused by the processes of sulfate reduction and methane generation. Based on the balance relationships, an equation was constructed connecting changes in alkalinity with variations of Ca2+, SO42+, and NH4+ in interstitial solutions.